2014
DOI: 10.1073/pnas.1401006111
|View full text |Cite
|
Sign up to set email alerts
|

Molecular tracing of the emergence, diversification, and transmission of S. aureus sequence type 8 in a New York community

Abstract: During the last 2 decades, community-associated methicillinresistant Staphylococcus aureus (CA-MRSA) strains have dramatically increased the global burden of S. aureus infections. The pandemic sequence type (ST)8/pulsed-field gel type USA300 is the dominant CA-MRSA clone in the United States, but its evolutionary history and basis for biological success are incompletely understood. Here, we use whole-genome sequencing of 387 ST8 isolates drawn from an epidemiological network of CA-MRSA infections and colonizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
191
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(232 citation statements)
references
References 49 publications
37
191
2
Order By: Relevance
“…It is unclear if any of the listed mutations are important for colonization of the nares or infection of the wound. Curiously, one of the mutations in the (30). The tree in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is unclear if any of the listed mutations are important for colonization of the nares or infection of the wound. Curiously, one of the mutations in the (30). The tree in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the infections were due to a single MRSA clone, USA300, which is currently the most prevalent clone of CA-MRSA in the United States and specifically in New York City (30). ACME was restricted to strains belonging to the USA300 CA-MRSA clone or clones closely related to it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clade CC8-A also carries the PVL-associated genes and contains isolates that belong to the USA300 clone. In a study investigating the genomics of USA300, Uhlemann et al found evidence for at least five different acquisitions of the lukSF-carrying prophage into the ST8 population, but only a single event into USA300 clone [47]. From their phylogenomic analysis, the authors concluded that acquisition of the lukSF-carrying prophage coincided with the acquisition of ACME and occurred between 1970 and 1993, resulting in the emergence of USA300.…”
Section: Community-associated Meticillin-resistant Staphylococcus Aurmentioning
confidence: 99%
“…5) (9,(211)(212)(213). Comprehensive reviews address the essentially clonal population structure of S. aureus (214)(215)(216) and other staphylococcal species (207) and also the impact of HGT in the evolutionary history of staphylococcal populations (9,(217)(218)(219), with emphasis on the description of the plasmids associated with AbR genetic elements (9,51,84,220) and their influence on the variability of lineages (217,219,(221)(222)(223)(224).…”
Section: Staphylococcimentioning
confidence: 99%